Measurement of digital video broadcasting-second generation terestrial (DVB-T2) signal in Kuala Lumpur, Malaysia - Norsuzila Ya’acob; Noraisyah Tajudin; Mashira Meri @ Mohamad Zamiri; Azita Laily Yusof; Suzi Seroja Sarnin; Azlina Idris (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
DVB-T2 (Digital Video Broadcasting – Second Generation Terrestrial) is one of the latest technical standards being developed by the DVB Project for DTT (Digital Terrestrial Television). It is also known as digital broadcasting trough terrestrial system since 2006 and is an extension of the DVB-T system as a second generation program to improve efficiency of the total system.  It is important to perform a research on the performance of DVB-T2 because Malaysia has launched the free-to-air digital TV project since 2016 hence there is a need to know how well the signal is being received by viewers. This research focuses on a DVB-T2 transmission process which involve the transmission from Menara Kuala Lumpur transmitter to receivers located at 100 different locations. The performance of DVB-T2 can be determined by measuring the field strength, MER (Module Error Ratio) and BERaLDPC (Bit Error Rate after Low Density Parity Check decoder), and then a comparison between DVB-T and DVB-T2 systems can be made.  Equipments involved in the measurement are indoor antenna, distribution amplifier, waveform monitor, field strength meter, DVB-T2 decoder and TV set as the receiver. Results are recorded in Microsoft Excel and analyzed using MATLAB software. The result of the measurement shows92% of the test points had higher reading than the baseline value which means better reception of digital TV signal is delivered to the location.Comparison between DVB-T and DVB-T2 performance shows that field strength of the DVB-T2 system is slightly higher by 1.5 % – 3.8 % from DVB-TMeasurement of digital video broadcasting-second generation terestrial (DVB-T2) signal in Kuala Lumpur, Malaysia